Human Food Safety Implications of Variation in Food Animal Drug Metabolism - Lin, Zhoumeng; Vahl, Christopher I.; Riviere, Jim E. (My University, 2017)
Violative drug residues in animal-derived foods are a global food safety concern. The use of a fixed main metabolite to parent drug (M/D) ratio determined in healthy animals to establish drug tolerances and withdrawal times in diseased animals results in frequent residue violations in food-producing animals. We created a general physiologically based pharmacokinetic model for representative drugs (ceftiofur, enrofloxacin, flunixin, and sulfamethazine) in cattle and swine based on extensive published literature. Simulation results showed that the M/D ratio was not a fixed value, but a time-dependent range. Disease changed M/D ratios substantially and extended withdrawal times; these effects exhibited drug-and species-specificity. These results challenge the interpretation of violative residues based on the use of the M/D ratio to establish tolerances for metabolized drugs.
Citation: Lin, Z., Vahl, C. I., & Riviere, J. E. (2016). Human Food Safety Implications of Variation in Food Animal Drug Metabolism. Scientific Reports, 6. doi:10.1038/srep27907